A critical review of pretreatment technologies to enhance anaerobic digestion and energy recovery. (15th June 2020) - Atelge, M.R.; Atabani, A.E.; Banu, J. Rajesh; Krisa, David; Kaya, M.; Eskicioglu, Cigdem; Kumar, Gopalakrishnan; Lee, Changsoo; Yildiz, Y.Ş.; Unalan, S.; Mohanasundaram, R.; Duman, F.
Graphical abstract: Highlights: Pretreatments are important in a combined biorefinery aspect with different waste resources. Components of substrates are taken in account to improve pretreatment efficiency. Combined pretreatment is a suitable solution to improve the digestibility. Biogas yield and energy balance should be considered for the effects of pretreatments. Abstract: Biogas production from different waste resources still has limitations due to its complex structure and slowly biodegradable nature. To improve methane yield and anaerobic digestion performance, various substrate pretreatment methods have been suggested. This paper reviews the latest trends, progress, and research achievements about pretreatment technologies to improve anaerobic digestion efficiency. The pretreatment techniques are divided into four main groups which are physical, chemical, biological, and combined. The effect of inhibitor formation during the pretreatment process is discussed. The energy performance, economics, and environmental impact of these pretreatment technologies are revealed. This study concludes with future trends and emphasizes the necessity of pretreatment methods.